2016
DOI: 10.1136/bmjdrc-2016-000310
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diabetic nephropathy and depression: a cross-sectional analysis using the Diabetes Study from the Center of Tokyo Women's Medical University (DIACET)

Abstract: ObjectiveWe conducted this cross-sectional study to investigate the relationship between stage of diabetic nephropathy and likelihood or severity of depression in patients with diabetes.Research design and methodsWe studied 2212 patients with diabetes (mean age 60.9 years; 928 women; 1838 patients with type 2 diabetes). Presence and severity of depression was examined using the Patient Health Questionnaire-9 (PHQ-9). Patients were classified into 5 stages of nephropathy, according to albuminuria and estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
2
20
0
2
Order By: Relevance
“…Takasaki et al stated that nephropathy is likely associated with increased depression, which is actually decreased following kidney transplant. 53 Another study stated that not only did retinopathy worsen the presence of depression in diabetic patients but also the depression itself worsened the retinopathy in return. 54 As for strokes, it was well established that history of type 2 DM and a past cardiovascular accident event were highly predictive of depression and could even lead to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Takasaki et al stated that nephropathy is likely associated with increased depression, which is actually decreased following kidney transplant. 53 Another study stated that not only did retinopathy worsen the presence of depression in diabetic patients but also the depression itself worsened the retinopathy in return. 54 As for strokes, it was well established that history of type 2 DM and a past cardiovascular accident event were highly predictive of depression and could even lead to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Yu suggested that depression is associated with proinflammatory cytokines and this proinflammatory state has been linked with an increased risk of diabetic nephropathy. Takasaki (2016) also found that the progression of diabetic nephropathy is likely to be associated with increased risk and severity of depression [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individuals with diabetes have a 2–4 fold greater risk of depression when compared to individuals without diabetes 7 . Depression is associated with higher glycated haemoglobin (HbA1c) 8 , higher rates of complications 9 , 10 and mortality 11 . This association may be mediated by sub-optimal self-care 12 , medication adherence 13 , health-related quality of life 14 and common pathophysiological mechanisms via stress and inflammation 7 .…”
Section: Introductionmentioning
confidence: 99%